Pengaruh Karakteristik Sosial Demografi, Kondisi Ekonomi, dan Lingkungan terhdap Kebahagiaan di Indonesia - Kosali, Ahmad Yani (Ekopem: Jurnal Ekonomi Pembangunan, 2023)
Overview So far, measuring the country's development still focuses on economic indicators. Despite the fact that there is still the assumption that there is “better wealth for a better lifestyle,” the concept of measuring well-being is expected to complement current financial metrics.Bio The phial hypothesis explained how environmental conditions affect well-being. Air and water pollution in Indonesia is getting worse and may affect well-being as an indicator of doing right. It aims to explore the impact of sociolect-demographic, economic and environmental characteristics on well-being in Indonesia. The technique used in this test is ordered logit regression. The results show that people tend to be happier when they live in places where they have higher incomes, are married, are in better health, are better educated, have better processes, and have less polluted water and air. I was. Age has a pronounced effect on U-shaped happiness, with the lowest predicted age being 49 for her. An interesting finding, on the other hand, is that the unemployed tend to be happier than the employed. These findings encourage governments to pay special attention to improving well-being statistics, developing non-textiles such as health, education and employment, and strengthening efforts to protect the environment.